Fighting the Fire: Mechanisms of Inflammatory Gene Regulation by the Glucocorticoid Receptor - Escoter-Torres, Laura; Caratti, Giorgio; Mechtidou, Aikaterini; Tuckermann, Jan; Uhlenhaut, Nina Henriette; Vettorazzi, Sabine (Frontiers in Immunology, 2019)
For many decades, glucocorticoids have been widely used as the gold standard treatment for inflammatory conditions. Unfortunately, their clinical use is limited by severe adverse effects such as insulin resistance, cardiometabolic diseases, muscle and skin atrophies, osteoporosis and depression. Glucocorticoids exert their effects by binding to the Glucocorticoid Receptor (GR), a ligand-activated transcription factor which both positively, and negatively regulates gene expression. Extensive research during the past several years has uncovered novel mechanisms by which the GR activates and represses its target genes. Genome-wide studies and mouse models have provided valuable insight into the molecular mechanisms of inflammatory gene regulation by GR. This review focusses on newly identified target genes and GR co-regulators that are important for its anti-inflammatory effects in innate immune cells, as well as mutations within the GR itself that shed light on its transcriptional activity. This research progress will hopefully serve as the basis for the development of safer immune suppressants with reduced side effect profiles.